1968
DOI: 10.1017/s0043174500047433
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine-Induced Ultrastructural Changes of Barnyardgrass Chloroplasts

Abstract: Electronmicrographs of barnyardgrass (Echinochloa crusgalli (L.) Beauv.) grown under controlled conditions and treated with 2-chloro-4-ethylamino-6-isopropylamino-s-triazine (atrazine) at the one to three-leaf stages show that degradation of the chloroplast starts as a swelling of the fret system followed by swelling and disruption of the granal discs. In advanced stages of breakdown, the membranes of the grana and chloroplast envelope were ruptured. These changes were initiated 2 hr after treatment with rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…These results confirm the observations by Ashton et al (1963) on kidney bean (C3 plant) and Hill et al (1968) on barnyardgrass (C 4 plant). Both these species have chloroplasts similar to the mesophyll chloroplasts of maize (C4) and are characterized by an extensive intergranal fret system.…”
Section: Mesophyll Chloroplasts Of Treated Plantssupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirm the observations by Ashton et al (1963) on kidney bean (C3 plant) and Hill et al (1968) on barnyardgrass (C 4 plant). Both these species have chloroplasts similar to the mesophyll chloroplasts of maize (C4) and are characterized by an extensive intergranal fret system.…”
Section: Mesophyll Chloroplasts Of Treated Plantssupporting
confidence: 91%
“…Subsequent leaves usually develop normally. The ultrastructure of kidney bean and barnyardgrass chloroplasts has been described by Ashton et al (1963) and Hill et al (1968). Mesophyll-type chloroplasts in maize plants are similar in structure to those of barnyardgrass as described by the above-mentioned authors.…”
Section: Resultsmentioning
confidence: 72%
“…Effects on chloroplasts similar to those described here may be caused by environmental factois such as the movement of plants from darkness to light, and by zinc deficiency (Weier et al, 1963). Hill, Putala & Venegris (1968) also observed that leaf mineral deficiency could modify grana and fretwork structure in chloroplasts. In this study, chloroplasts and cell membranes of control tissues were unaffected by environmental conditions and the results described for Tordon 50D-and Tordon 22K-trcatcd tissues were permanent and due solely to herbicide treatment.…”
Section: Diseussionsupporting
confidence: 80%
“…Starch was not found in the chloroplasts of any of the plants, which indicated either an altered photosynthesis or the utilization of carbohydrates. Absence of starch has been reported by Ashton et al (1963) and Hill et al (1968) in plants treated with atrazine. Geronimo and Herr (1970) reported the disappearance of starch from tobacco chloroplasts after pyroclor treatment, Anderson and Schaelling (1970) with pyrazon, and Meier and Lichtenthaler (1981) with bentazon.…”
Section: Umrastnicturementioning
confidence: 90%